Negative Pressure Dressings over Free Muscle Flaps with Immediate Split-Thickness Skin Grafting: A 9-Year Experience - Kumbla, Pallavi A.; Henry, Steven L.; Boyd, Carter J.; Kelley, Patrick K.; Thorburn, Ashley Q.; Myers, René P. (Journal of Reconstructive Microsurgery Open, 2020)
Background Negative pressure wound therapy has allowed for significant advances in the treatment of wounds. This occurs through a process of angiogenesis, microdeformation, macrodeformation, and decrease in exudate and bacterial load. It is routinely used as a bolster in the management of skin grafts. However, its role as a dressing over free muscle flaps has not gained widespread acceptance due to the fear of flap compromise.Methods A retrospective review of 97 patients over 9 years was performed. All patients underwent free muscle flap coverage of various wounds with immediate split-thickness skin grafting. A negative pressure dressing was applied, with windows made in the foam sponge to enable Doppler monitoring as well as visual inspection of the flap. Complications including flap failure, skin graft loss, hematoma, distal flap necrosis, negative pressure dressing failure, partial muscle necrosis, and mild flap congestion were assessed.Results Flap loss occurred at a rate of 8.2% (eight flaps). Four of these flaps were lost due to patient factors not attributable to the dressing. In the remaining four flaps (4.1% of the series), it is conceivable that the negative pressure dressing was a contributing factor. However, this failure rate is comparable to flap loss rates in studies where negative pressure dressings were not used. The rates of skin graft failure, hematoma, distal flap necrosis, inability to maintain seal, partial muscle necrosis, and mild flap congestion were also acceptable and similar to studies where negative pressure dressings were not used.Conclusion Negative pressure dressings over free muscle flaps with immediate split-thickness skin grafts are effective and safe to use while allowing for postoperative flap monitoring and skin graft protection.
Keywords: negative pressure dressing; free muscle flap; split-thickness skin graft